A Comparative Study of the Penal Dissolution of Concession Contracts for Public Works and Supplies under Jordanian Law - AL-mwas, Barah Naif (Dirasat: Shari'a and Law Sciences, 2023)
Objectives: This study aims to clarify the Jordanian legislature and judiciary's position on penal dissolution as it relates to Public Works and Supply Contracts. Specifically, it examines the recognition of the administration's power of penal dissolution and the subjection of this authority to judicial control to ensure that it is not arbitrary. Methods: The study adopted the comparative descriptive analytical approach, where the relevant Jordanian legal texts and judicial rulings and comparing them to the positions of French and Egyptian legislation and judiciary. The goal is to reach practical results that align with the study's objectives. Results: That study found that Jordanian, French, and Egyptian legislators did not grant the parties of the contract the right to appeal against the decision to terminate the administrative contract. However, the Jordanian and Egyptian judiciary allowed appeals against the annulment of administrative decisions issued during the contract's negotiation stage, excluding those made during the contract's execution. However, the French judiciary allowed third parties to appeal the annulment of all decisions related to the administrative contract. Conclusions: The study recommends that the Jordanian legislature include an article in the Administrative Justice Law that allows contractors to appeal against the decision to terminate the administrative contract by annulment. Doing so would encourage individuals to contract with the administration.